Sexual Function in Women with Stress Urinary Incontinence Treated with the SPARC Sling System. (14th July 2013) - Mohamad Al-Ali, Badereddin; Shamloul, Rany; Hutterer, Georg C.; Puchwein, Erika; Pummer, Karl; Avian, Alexander; Primus, Günter
Abstract : Aim . To evaluate the impact of SPARC on female sexual function. Methods . 151 women with a mean age of 60 ± 11.90 and SUI had a complete urodynamic investigation and underwent SPARC operation. 98 women completed the validated female sexual function index questionnaire (FSFI) at baseline and 94 women at follow-up. A minimum follow-up of 12 months was required for study inclusion. Results . 52/98 women were sexually active at baseline. Postoperatively only 33 patients were sexually active. The FSFI score of all 33 pre- and postoperative sexually active women increased from 25.3 ± 5.7 at baseline to 27.4 ± 4.8 at follow-up (P = 0.1 ). Scores of women with reduced sexual function at baseline increased significantly in the domains desire, arousal, and lubrication as well as orgasm and satisfaction and total FSFI-score (P = 0.002 ) postoperatively. Conclusions . Our results suggest that the SPARC-sling procedure for SUI did not negatively interfere with female sexual function.